The Influence of Electronic Health Education Media on Enhancing Self-Management Among Individuals Afflicted with Gout Arthritis: A Comprehensive Scoping Review - Sandehang, Cornelia Fransiska (Journal of Nursing Science Update (JNSU), 2024)
Monosodium urate crystals accumulate in Gout Arthritis, resulting in joint inflammation, significant pain, and potential joint damage, which can impair mobility and lead to disability. Additionally, uncontrolled hyperuricemia may result in the formation of kidney stones and diminished kidney function. Therefore, implementing effective management and treatment strategies is crucial for enhancing self-management in individuals diagnosed with Gout Arthritis. This scoping review seeks to provide an overview of the effectiveness of various electronic health education media in improving the self-management of individuals suffering from Gout Arthritis. The study followed the PRISMA guidelines for scoping reviews and involved a comprehensive literature search across ProQuest, Science Direct, Wiley, and Google Scholar, focusing on publications from 2016 to 2022. Ten articles that met the predetermined inclusion criteria were synthesized for this review. The findings suggest that using electronic health education media can significantly enhance self-management practices and medication adherence among Gout Arthritis patients and facilitate favourable changes in uric acid levels. These insights may serve as valuable contributions to managing Gout Arthritis cases